Strengthening Maternal and Child Health Information Systems Management Policies: Study in Maluku Province - Asep Kusnali; Tety Rachmawati; Karlina Karlina; Istiana Hermawati; Haerawati Idris (Jurnal Organisasi dan Manajemen, 2024)
Purpose – The importance of maternal and child health data in enhancing health services has the problem of underutilization of collected data. It points out the challenges in using this information to make informed policy, program design, and resource allocation decisions. This study examines the challenges in utilizing maternal and child health data for policymaking in Maluku Province. Methodology – We apply a research qualitative approach using the WHO Health Metrics Network to assess the capacity of the health information system in Ambon and Buru. Findings – The research found that 70% of health data was underutilized due to data accuracy and integration issues. Based on detailed capacity assessments, a tailored health information system management framework was developed. Key findings include policy gaps and actionable recommendations to enhance data use in decision-making, aiming to improve health service delivery and outcomes. Originality – The study focuses on the unique challenges of maternal and child health data utilization in Maluku Province, Indonesia. The research addresses specific gaps in policy and strategy, human resource governance, and data integration by developing a health information system management framework and conducting capacity assessments.